2018
DOI: 10.3390/ma11101914
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Parabolic Superhydrophobic Material for Oil-Water Separation

Abstract: In order to prepare parabolic superhydrophobic materials, copper meshes were used as the substrate and ultrasonic etching and oxidative corrosion were carried out with FeCl3 solution and H2O2 solution, respectively, and then the surface was modified with stearic acid (SA). The topological structure and surface wettability of the prepared mesh were characterized by fluorescence microscope, scanning electron microscopy and contact angle measurement. Finally, the as-prepared copper meshes were applied to oil-wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The contact angle of the water droplets is less than 90 • . However, for hydrophobic surfaces, the droplets were not easily spread and appeared spherical on the surface, the contact angle of the water droplets is greater than 90 • [43]. It is generally believed that as the contact angle increases, the hydrophobic property improves.…”
Section: Hydrophobic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The contact angle of the water droplets is less than 90 • . However, for hydrophobic surfaces, the droplets were not easily spread and appeared spherical on the surface, the contact angle of the water droplets is greater than 90 • [43]. It is generally believed that as the contact angle increases, the hydrophobic property improves.…”
Section: Hydrophobic Performancementioning
confidence: 99%
“…From Table 1, the CA of the copper sheet modified with SA was always bigger than that of unmodified with SA. That was due to the low surface energy being a key factor in achieving superhydrophobicity [43]. The surface free energy can affect the value of the contact angle; the smaller the surface free energy is, the larger the contact angle is.…”
Section: Hydrophobic Performancementioning
confidence: 99%
“…Research on superhydrophobic [ 1 , 2 ], superoleophobic [ 3 , 4 ], superamphiphobic [ 4 , 5 , 6 , 7 ] and superoleophilic [ 8 , 9 , 10 ] surfaces has developed rapidly in recent years [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Meanwhile, an increasing number of applications for such surfaces, including self-cleaning [ 21 ], anti-fingerprint coatings [ 22 ], anti-fog coatings [ 23 ], microdroplet transfer technology [ 24 ] and oil–water separation [ 25 , 26 , 27 , 28 , 29 , 30 ], have been investigated. Superhydrophilic surfaces have been drawing extensive attention since Fujishima found that nanoscale TiO 2 possesses superhydrophilic properties when exposed to light and recovers its hydrophobic nature in the dark with cyclic reversibility [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from that, further applications and processes dependent on the wettability phenomenon include printing, adhesion, coating, lubrication, air conditioning, desalination, corrosion prevention, oil-water separation, anti-icing, food packaging, etc. [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%